Inheritance of SPAD chlorophyll meter reading and specific leaf area in four crosses of groundnut (Arachis hypogaea L.) - Janila, Pasupuleti; Manohar, Surendra Singh; Rathore, Abhishek; Nigam, Shyam Narayan (The Indian Journal of Genetics and Plant Breeding, 2016)
SPAD chlorophyll meter reading (SCMR) and specific leaf area (SLA) are important traits associated with water-useefficiency (WUE). Understanding their genetic nature and association with yield parameters enables their deployment in breeding programs for drought tolerance. The results obtained from the study conducted on six generations of four groundnut crosses showed significant additive effects for SCMR and SLA in all the crosses indicating possible gains through selection. Relative contribution of additive effects was high for both, SCMR (58 to 93%) and SLA (63 to 91%). The low heritability of SCMR and SLA indicates environmental influence on these traits. SCMR is positively associated with pod, kernel and haulm yield, while the association of SLA with them was negative. Combining trait-based approach using SCMR and SLA with empirical approach can be rewarding in groundnut breeding for drought tolerance.